Analisis Pajak Penghasilan Pasal 25: Mekanisme, Penghitungan, dan Kontribusinya terhadap Kepatuhan Pajak dan Penerimaan Negara - Ananda Fitriani Oktavia; Nazli Aulia; Salma Indriani (Pajak dan Manajemen Keuangan, 2025)
Article 25 Income Tax (PPh 25) is a tax payment system by taxpayers in the form of monthly installments aimed at alleviating the tax burden at the end of the tax year. This provision applies to both Individual Taxpayers and Entities, and is calculated based on the amount of tax owed in the previous year, reduced by tax credits. PPh 25 plays an important role in maintaining the smooth flow of state revenue and supporting sustainable tax compliance. This paper comprehensively discusses the legal basis, calculation mechanisms, payment timing, and penalties for late payment of PPh 25. This research also examines the effectiveness of PPh 25 in encouraging voluntary compliance and its contribution to state revenue.